2021
DOI: 10.1039/d1gc03191k
|View full text |Cite
|
Sign up to set email alerts
|

From green to blue economy: Marine biorefineries for a sustainable ocean-based economy

Abstract: Biorefinery is the ideal model to help marine industries to apply green and blue economy principles towards a more sustainable, profitable, and conscious ocean economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 157 publications
0
24
0
Order By: Relevance
“…[ 37 ] Algae and marine biorefineries are receiving increased attention in the scientific literature because of their untapped potential up to date, and could provide a new source of monomers and polymers in the future. [ 38,39 ]…”
Section: Top‐down: Biopolymers and Their Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37 ] Algae and marine biorefineries are receiving increased attention in the scientific literature because of their untapped potential up to date, and could provide a new source of monomers and polymers in the future. [ 38,39 ]…”
Section: Top‐down: Biopolymers and Their Monomersmentioning
confidence: 99%
“…[37] Algae and marine biorefineries are receiving increased attention in the scientific literature because of their untapped potential up to date, and could provide a new source of monomers and polymers in the future. [38,39] Another relevant fraction of biomass is lignin, which is the biggest source of biogenic aromatics available on Earth. The lignin biopolymer consists of a propylphenolic backbone based on three main building blocks-p-coumaryl, coniferyl and Biomass and other natural resources from which macromolecules can be extracted.…”
Section: Top-down: Biopolymers and Their Monomersmentioning
confidence: 99%
“…The development and implementation of a successful marine bio-refinery can meet the goals of a “greener” socioeconomic development, also termed “blue economy”; a term is used as a synonym for “sustainable ocean-based economy” ( 111 ). The development and implementation of a marine biorefinery can be fundamental to consolidate a “greener” socioeconomic oceanic development ( 112 ).…”
Section: Green Processes For the Recovery Of Proteinsmentioning
confidence: 99%
“…Veríssimo et al ( 112 ) observed that biorefineries are sophisticated multi-step systems, requiring expertise in all stages of manufacturing, in addition to a clear vision of all raw materials, residues, and products. The attributes of a marine biorefinery are low cost of raw material, comparatively simple processes, lower energy consumption, and high productivity ( 131 ).…”
Section: Green Processes For the Recovery Of Proteinsmentioning
confidence: 99%
“…Even though it is true that the waste biorefineries have been steadily increasing over the past years (mostly due to the adoption of the 2030 Agenda for Sustainable Development that obliges individual countries to take actions aimed at achieving the 17 goals of sustainable development) the same trend is not observed yet for the specific case of marine waste biorefineries [59].…”
Section: Shrimp Shells' Biorefinery Pipeline As a Businessmentioning
confidence: 99%